2021
DOI: 10.3390/atmos12101234
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Projected Urban Expansion on Rainfall and Temperature during Rainy Season in the Middle-Eastern Region in Tanzania

Abstract: Future changes of land use and land cover (LULC) due to urbanization can cause variations in the frequency and severity of extreme weather events, affecting local climate and potentially worsening impact of such events. This work examines the local climatic impacts associated with projected urban expansion through simulations of rainfall and temperature over the rapidly growing city of the middle-eastern region in Tanzania. Simulations were conducted using a mesoscale Weather Research and Forecasting (WRF) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…The results on the increase in rainfall during the OND season coincide with previous studies (Gulacha and Mulungu, 2017;Luhunga et al, 2018), which also projected an increase in rainfall over some parts of Tanzania including Dar es Salaam. Another study by Anande and Park (2021) reported a decrease in precipitation on wet days in urbanized areas including Dar es Salaam. Increased precipitation in coastal urban regions was mainly due to the strong updraft motion as there were large spatial variations in precipitation.…”
Section: Future Projection Monthly Cyclementioning
confidence: 95%
See 1 more Smart Citation
“…The results on the increase in rainfall during the OND season coincide with previous studies (Gulacha and Mulungu, 2017;Luhunga et al, 2018), which also projected an increase in rainfall over some parts of Tanzania including Dar es Salaam. Another study by Anande and Park (2021) reported a decrease in precipitation on wet days in urbanized areas including Dar es Salaam. Increased precipitation in coastal urban regions was mainly due to the strong updraft motion as there were large spatial variations in precipitation.…”
Section: Future Projection Monthly Cyclementioning
confidence: 95%
“…However, little has been carried out to determine climate variability and its associated extremes and impacts in the cities and towns with large populations and major economic activities. For example, Anande and Park (2021) examined the local climatic impacts associated with projected urban growth by simulating rainfall and temperature over the rapidly growing cities of the middle-eastern region in Tanzania. However, this study was only conducted for 10 days during the rainfall season in April 2018 and suggests further research to understand the effects of urbanization on the future climate in large cities.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1, the 40 studied urban areas are mostly located in North America, Asia, and Europe, almost all of them are in the northern hemisphere, and the majority of cities are in coastal areas. Still, during the selection of articles, we found a few of them focusing on the southern hemisphere, two studying African urban areas, Nairobi in Kenya (Ongoma et al, 2015), and the Middle-Eastern Region in Tanzania (Anande & Park, 2021), one in central America (Jauregui & Romales, 1996), two south American cities, San Miguel de Tucumán in Argentina and Manaus in Brazil (Freitag et al, 2018;Sátyro et al, 2021), and one article for Oceania investigating Australian urban areas (Rosenfeld, 2000). However, these listed articles could not be selected for the analysis in this article because of their methodology or dataset types descriptions, or inexplicit conclusions.…”
Section: Search String = (Ti = (Urban) or Ti = (City) Or Ti = (Cities...mentioning
confidence: 99%
“…Numerical models can induce errors but they are regularly validated against different datasets and they allow to reach fine spatial and temporal resolutions. Among the models used in the experiments, one model, in particular, is heavily used with its different possible parametrizations, the weather research and forecasting (WRF) model(Anande & Park, 2021;Argüeso et al, 2016;Debbage & Shepherd, 2019;Freitag et al, 2018;Kusaka et al, 2019;Luong et al, 2020;Miao et al, 2011;Niyogi et al, 2020;Ntelekos et al, 2008;Pathirana et al, 2014;Sarangi et al, 2018;Shem & Shepherd, 2009;Shimadera et al, 2015;Song et al, 2016;Supantha et al, 2018;Wang et al, 2016;Xiao et al, 2020;Zhong & Yang, 2015). However, the experiments using the WRF model are not directly comparable with each other because of the diversity of parametrization used.…”
mentioning
confidence: 99%